What makes oncogenes mutually exclusive?. (3rd July 2017) - Cisowski, Jaroslaw; Bergo, Martin O.
ABSTRACT: Cancer is driven by mutations in genes whose products participate in major signaling pathways that fuel cell proliferation and survival. It is easy to assume that the more of these so-called driver mutations a tumor accumulates, the faster it progresses. However, this does not appear to be the case: Data from large-scale genome sequencing studies indicate that mutations in driver oncogenes often are mutually exclusive. The mechanisms underlying the mutual exclusivity of oncogenes are not completely understood, but recent reports suggest that the mechanisms may depend on the tumor type, and the nature of interacting oncogenes. Here we discuss our recent findings that the oncogenes KRAS G12D and BRAF V600E are mutually exclusive in lung cancer in mouse models because their coexpression leads to oncogene-induced senescence.